2000
DOI: 10.1016/s0194-5998(00)70249-x
|View full text |Cite
|
Sign up to set email alerts
|

Head and neck squamous cell carcinoma: Better to be young

Abstract: Most head and neck squamous cell carcinoma patients are elderly, with few younger than 40 years. Controversy exists in the literature regarding outcomes for younger patients. The goal of this research project was to compare baseline features and outcomes for young patients (/=65 years). To investigate the relationship between age and important presenting features and outcomes, 1160 recently diagnosed patients first treated at Washington Unive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
57
2
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(72 citation statements)
references
References 32 publications
5
57
2
1
Order By: Relevance
“…Fridllander et al [8], Pitman et al [9], Vargas et al [10], Glory et al [11] and Pytynia et al [12] noted that there were no significant differences in outcome between the different age groups. However, McGrefor et al [13], Clark RM et al [14], Hafkamp et al [15], Carniol and Fried [16], and Lacy PD et al [17] all showed that the prognosis for young patients was better. Because of the disparity in the results of these studies, the question of outcome between different age groups remains unanswered.…”
Section: Introductionmentioning
confidence: 99%
“…Fridllander et al [8], Pitman et al [9], Vargas et al [10], Glory et al [11] and Pytynia et al [12] noted that there were no significant differences in outcome between the different age groups. However, McGrefor et al [13], Clark RM et al [14], Hafkamp et al [15], Carniol and Fried [16], and Lacy PD et al [17] all showed that the prognosis for young patients was better. Because of the disparity in the results of these studies, the question of outcome between different age groups remains unanswered.…”
Section: Introductionmentioning
confidence: 99%
“…These tumors are locally invasive, with frequent metastasis both to regional and distant organs [3]. Despite significant advances in therapeutic modalities treatment regimens, the presence of metastasis remains the major determinant of poor outcome for patients with OSCCs [4,5], and the survival rate is among the lowest of the major cancers [6].…”
Section: Introductionmentioning
confidence: 99%
“…In young patients with head and neck SCC, the oral tongue is the most common primary site 22,25,26. We report the outcomes of a pediatric cohort of patients with SCC of the oral tongue who were treated at a comprehensive cancer center and compare outcomes with those of an adult cohort matched for sex, smoking history, stage, and treatment modality.…”
mentioning
confidence: 99%